2007
DOI: 10.5367/000000007782696032
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Specialization and Environmental Sustainability in a Dynamic Economy

Abstract: This study focuses on the dynamic behaviour of a small open economy specialized in tourism based on natural resources. The author analyses the steady-state properties in two scenarios, with and without public abatement expenditures, and a unique local saddle-point equilibrium is found for both cases. The analysis of the dynamics provides an alternative explanation for the observed positive growth performance of small open tourism-based economies and for the worldwide increases in tourist inflows, which are see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 25 publications
3
55
1
6
Order By: Relevance
“…Our model and the results add to the existing literature (e. g., Piga (2003), Pintassilgo and Silva (2007), Candela et al (2007), Cerina (2007), Gómez et al (2008)), as the model uses a general equilibrium framework with considers the international financial market too, and as the analysis is not restricted by using particular functional forms. We thus can show that and how the tax rate has to be intertemporally adjusted.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Our model and the results add to the existing literature (e. g., Piga (2003), Pintassilgo and Silva (2007), Candela et al (2007), Cerina (2007), Gómez et al (2008)), as the model uses a general equilibrium framework with considers the international financial market too, and as the analysis is not restricted by using particular functional forms. We thus can show that and how the tax rate has to be intertemporally adjusted.…”
Section: Resultssupporting
confidence: 58%
“…6 Recently there is a growing literature in tourism economics using models which apply dynamic optimization methods, see, e. g., Hazari and Sgro (2004, ch. 12), Chao et al (2005), Candela and Cellini (2006), Cerina (2007), Faria (2008), Schubert and Brida (2008), and Gómez et al (2008).…”
Section: A1 Dynamics Of Bonds B I (T)mentioning
confidence: 99%
“…5.2. References used to compile the compendium of factors found in previous studies to influence the likelihood of returning, tourist trip satisfaction and overall trip satisfaction Probability that a tourist will return Tourist's overall trip satisfaction Overall satisfaction with life Country of origin Assaker & Hallak, 2012;Hui et al, 2007;Saltzer, 2002b) Kozak & Rimmington, 2000; Trip cost/perceived value for money Petrick et al, 2001;Randriamboarison et al, 2013;Saltzer, 2002b) Peace, quiet and not overcrowded found important by , , Brau and Cao (2008), Cerina (2007), Hern andez and Le on (2007) (Kountouris & Remoundou, 2011;Welsch, 2007b) (Demos, 1992;Handszuh, 2006;Tarlow, 2006).…”
Section: Acknowledgementsmentioning
confidence: 98%
“…While on one side tourism literature finds evidences on the positive role of tourism for economic growth, on the other side, it stresses the potential negative effects of a possible overproduction: in attractive locations, tourists and residents compete for the use of natural amenities along with a long list of public and private services, as a result, an unbalanced number of visitors may generate a switch of the virtuous economic cycle into a vicious one via the generation of many types of negative externalities. Shubert (2009, pp.3-4) (Budowski, 1976;Liu, Sheldon and Var, 1987;Dwyer and Forsyth, 1993;Chao, Hazari and Sgro, 2004;Cushman et al 2004;Aguilò et al, 2005;Cerina, 2007) or at the change in the residents attitude towards tourism (Akis et al, 1996;Faulkner and Tideswell, 1997;Johnson, 1997, 1999;Haralambopoulos and Pizam, 1996;Figini et al, 2007). Little attention is given to the possible negative externalities arising from the increase of crime in tourist destinations.…”
Section: Introductionmentioning
confidence: 99%